Invasive Fungal Sinusitis: Risk Factors for Visual Acuity Outcomes and Mortality - Hirabayashi, Kristin E; Idowu, Oluwatobi O; Kalin-Hajdu, Evan; Oldenburg, Catherine E; Brodie, Frank L; Kersten, Robert C; Vagefi, M Reza (Ophthalmic plastic and reconstructive surgery, 2019)
Invasive fungal sinusitis is a rare but potentially lethal disease that primarily affects immunocompromised patients. The purpose of this study was to review an academic medical center's experience in the presentation, diagnosis, and treatment of invasive fungal sinusitis. A retrospective chart review was performed at a single institution over a 17-year period. Medical records, radiographic imaging, and operative reports were analyzed. Bivariate and multivariable analyses were performed to determine factors that affected visual acuity outcomes and mortality. Fifty-five patients with histopathologically confirmed invasive fungal sinusitis were included. The average duration of follow up was 1.8 ± 2.6 years (range: 1 week to 10 years). The most common causes of immunosuppression were hematologic malignancy (45%), diabetes (31%), and organ transplantation (9%). At presentation, 35% of individuals were neutropenic (absolute neutrophil count < 500/μl). All patients received systemic antifungal treatment. A surgical intervention was performed on 50 patients (91%), and all but one had functional endoscopic sinus surgery. Nine (16%) patients underwent orbital exenteration. Multivariable analysis of visual acuity outcomes demonstrated that individuals infected with Zygomycota had 6-7 lines worse vision than those infected with Ascomycota (mean difference in logMAR 0.66, 95% confidence interval 0.27 to 1.06, p = 0.001). Patients who had functional endoscopic sinus surgery had 7-8 lines better visual acuity than those without functional endoscopic sinus surgery (mean difference in logMAR -0.76, 95% confidence interval -1.13 to -0.38, p < 0.001). The overall death rate due to infection was 24%. Bivariate models demonstrated no difference in mortality in patients receiving exenteration versus those who did not (p = 0.14). Multivariable analysis of mortality demonstrated that neutropenia increased mortality (adjusted odds ratio 10.05, 95% confidence interval 1.49 to 67.67, p = 0.02). Having a greater number of surgeries was associated with an increased rate of survival (adjusted odds ratio 0.39, 95% confidence interval 0.15 to 0.96, p = 0.04). Invasive fungal sinusitis is an aggressive disease with significant mortality. Patients with neutropenia had a lower rate of survival, and infection with Zygomycota was associated with worse visual acuity outcomes. Those having functional endoscopic sinus surgery had better final visual acuity, and an increased number of surgeries was associated with a decreased chance of death. Exenteration yielded no observed survival benefit.Endoscopic sinus debridement portends better visual acuity outcomes in patients with invasive fungal sinusitis, whereas exenteration yields no difference in survival benefit.